HUBUNGAN ANTARA KOMITMEN ORGANISASIONAL DAN GAYA MANAJEMEN KONFLIK KARYAWAN BANK MILIK PEMERINTAH DAERAH TINGKAT II DI PROVINSI DIY - Kristanto, Heru (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The aim of this study is to examine the impact of employee commitment on conflict management style with object,  circumstances,  and  conditions  of  Indonesia.  The  respondent  of  this  study  is  261  employees  of government-owned banks from five regencies in the Province of Daerah Istimewa Yogyakarta. The data were analized by implementing Multiple Linear Regression Technique. The results show that there is an indication that  employees  who  have  both  commitment  to  the  community  and  to  the  supervisor  tends  to  implement integrating and avoiding style. Employees who have a commitment to superior, tends to carry out domi nating and  obliging  approach.  Whereas,  employees  who   have  a  commitment  to  society,  tend to  implementing compromising approach. Implication of this study for future research is carry out longitudinal or ex perimental study.
Keywords: conflict management style, organizational commitment, longitudinal, experiment